Zonasi Tingkat Kerentanan Gempa Bumi Berdasarkan Faktor Lingkungan, Fisik, Sosial, dan Ekonomi di Kota Bandung Tahun 2018 - Denaner Pratama; Yasin Yusup; Sarwono Sarwono (Universitas Sebelas Maret (UNS), 2020)
This research aims to: 1) identify earthquake vulnerability in Bandung City based on 4 factors—environmental, physical, economical, and social—using Analytical Hierarchy Process (AHP); 2) understand which factor gives the biggest impact toward earthquake vulnerability of Bandung City; and 3) know Bandung City’s alertness toward earthquake. The population of this research was Bandung City’s administrative area with sub-district as its smallest analysis unit. Purposive sampling is used to collect sample. The data were collected from notes and maps, such as land use, slope, lithology, building density, etc. Interview also used to collect data for weighting using AHP. Data’s validity tested using triangulation. AHP’s used as data’s analysis technique. The result showed that: 1) The Earthquake Vulnerability in Bandung City based on physical, environmental, social, and economical factors were very high, high, and medium; 2) Physical factor, which is building density, gave the most impact to earthquake vulnerability in Bandung City; 3) Existing non-structural mitigation was deemed appropriate to earthquake vulnerability in Bandung City, but structural mitigation was not. Further structural review is needed.